St. Mary's Collegiate Church, Youghal, south choir wall, piscina, jamb, arch and hood - O'Donovan, Danielle (My University, 2008)
Piscina jamb and arch moulding, which comprises, from intrados: chamfer, flat surface, roll, broad fillet at same level as intrados, ogee, ogee, chamfer, fillet, ogee. The hood, from outermost point to innermost comprises: fillet, wave, hollow, ogee. This moulding is unusual for the inclusion of a wave, for the extra ornamentation of the intrados, and for the small proportion of the elements, which are similar to the sedilia in resembling the west door of Abbeydorney.
Piscina
Keywords: Architecture, Gothic -- Ireland; Cork (Ireland)--Buildings, structures, etc.; Youghal (Cork, Ireland); Collegiate churches; Late Medieval; roll moldings; moldings, hollow; moldings, ogee